2021
DOI: 10.1186/s13287-021-02473-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mesenchymal stromal cells from peritoneal dialysis effluent with those from umbilical cords: characteristics and therapeutic effects on chronic peritoneal dialysis in uremic rats

Abstract: Background A long-term of peritoneal dialysis (PD) using a hypertonic PD solution (PDS) leads to patient’s peritoneal membrane (PM) injury, resulting in ultrafiltration failure (UFF) and PD drop-out. Our previous study shows that PD effluent-derived mesenchymal stromal cells (pMSCs) prevent the PM injury in normal rats after repeated exposure of the peritoneal cavity to a PDS. This study was designed to compare the cytoprotection between pMSCs and umbilical cord-derived MSCs (UC-MSCs) in the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
(100 reference statements)
0
9
1
Order By: Relevance
“…Similar effectiveness in the protection of PM from PD solution-induced injury and dysfunction was observed in a rat model of biologically incompatible PDS induction upon treatment with PD effluent-derived MSCs [ 120 ]. MSCs can indeed be obtained from discarded PD effluent [ 121 ], which may provide a practical unlimited source of MSCs [ 122 ]. It has to be noted that in preclinical studies the improved PF by use of SCs was associated with an improvement in peritoneal permeability function, as assessed by peritoneal UF, glucose transport, and solute permeability [ 116 ].…”
Section: Combating Pd-solution Associated Toxicitymentioning
confidence: 99%
“…Similar effectiveness in the protection of PM from PD solution-induced injury and dysfunction was observed in a rat model of biologically incompatible PDS induction upon treatment with PD effluent-derived MSCs [ 120 ]. MSCs can indeed be obtained from discarded PD effluent [ 121 ], which may provide a practical unlimited source of MSCs [ 122 ]. It has to be noted that in preclinical studies the improved PF by use of SCs was associated with an improvement in peritoneal permeability function, as assessed by peritoneal UF, glucose transport, and solute permeability [ 116 ].…”
Section: Combating Pd-solution Associated Toxicitymentioning
confidence: 99%
“…The secretome and soluble factors from pMSCs have shown a significant decrease in PMC death when exposed to PDS [ 36 ]…”
Section: Sources Of Stem Cells and New Treatmentsmentioning
confidence: 99%
“…In vitro incubation with pMSC-conditioned medium (CM) prevented death in cultured human PMCs (HPMCs) and decreased proinflammatory gene expression while increasing anti-inflammatory gene expression [ 64 ]. A study by Du et al [ 36 ] published in 2021 showed that compared to UC-MSCs, pMSCs may more potently prevent PDS-induced PM injury; this effect is associated with higher resistance of pMSCs than UC-MSCs to uraemic toxins in culture and a greater reduction in PMC death by the secretome and soluble factors from pMSCs than by those from UC-MSCs in response to PDS exposure. The pMSCs represent a relatively novel type of SCs that are closely related to the peritoneum, and their relatively convenient accessibility and considerable therapeutic effects have made them promising options for anti-PF approaches.…”
Section: Sources Of Stem Cells and New Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study hope that drug programmes will be further modified to ensure greater accessibility to modern therapies in Poland for patients with rheumatic diseases. Due to the loss of patent protection of key TNFa inhibitors in rheumatology, such as adalimumab, etanercept and infliximab, bioequivalent drugs are the fastest growing group of therapies and offer the greatest hope for lower therapy costs [27]. Based on the current provisions of the Reimbursement Act, which qualify the inclusion of a bioequivalent drug in reimbursement and oblige the responsible entity to reduce the price of the bioequivalent drug by at least 25% compared to the price of the reference drug, it can be expected that the cumulative savings for the public payer from the introduction of bioequivalent drugs for monoclonal antibodies and fusion/soluble receptor proteins will be more than EUR 100 million per year in Poland.…”
Section: Drug Programmes In Polandmentioning
confidence: 99%